Why can parents’ phubbing affect mobile phone addiction? Perspective of the I-PACE model - Liu, Bo; Xu, Hemuqing; Wei, Hua; Song, Yuancai (Frontiers in Psychiatry, 2025)
ObjectiveBased on the I-PACE model, this study investigated the longitudinal relationship between parents’ phubbing and mobile phone addiction, as well as the serial mediating effects of maladaptive cognition and ego depletion.MethodsA longitudinal study, with data collected at two time points over a six-month interval to test the proposed hypotheses. The independent variable was measured at Time 1 (T1), while the mediators and dependent variables were assessed at Time 2 (T2). A total of 591 middle school students from a city in central China was recruited to complete the parents’ phubbing scale, maladaptive cognition scale, ego depletion scale and mobile phone addiction scale.Results(1) The correlation analysis showed a significant positive correlation between T1 parents’ phubbing, T2 maladaptive cognition, T2 ego depletion, and T2 mobile phone addiction. (2) Maladaptive cognition was found to mediate the relationship between parent’s phubbing and mobile phone addiction. Similarly, ego depletion also mediated the relationship between parent’s phubbing and mobile phone addiction. Additionally, both maladaptive cognition and ego depletion functioned as serial mediators between parent’s phubbing and mobile phone addiction.ConclusionThis study provides evidence that parental phubbing serves as a longitudinal predictor of mobile phone addiction, with maladaptive cognition and ego depletion acting as key mediators in this process.